A hundred billion trillion stars - Fishman, Seth; Greenberg, Isabel (New York, NY : Greenwillow Books, an imprint of HarperCollinsPublishers, 2017)
"A look at the numbers that surround us, big and small, on earth and in outer space."-
"Can you imagine so many ... of anything?"--Cover.
Ages 4-8.
K to grade 3.
Keywords: Mathematics -- Miscellanea -- Juvenile literature; Cardinal numbers -- Miscellanea -- Juvenile literature; Mathematics -- Miscellanea -- Pictorial works -- Juvenile literature; Cardinal numbers -- Miscellanea -- Pictorial works -- Juvenile literature; Picture books; Trivia and miscellanea; Mathematics -- Miscellanea; Cardinal numbers -- Miscellanea; JUVENILE NONFICTION -- Concepts -- Counting & Numbers; JUVENILE NONFICTION -- Mathematics; JUVENILE NONFICTION -- Science & Nature; Cardinal numbers; Mathematics; Mathematics -- Miscellanea -- Juvenile literature; Trivia and miscellanea; Juvenile works; Miscellanea; Trivia and miscellanea